Mobilization of CD11b+/Ly6chi monocytes causes multi organ dysfunction syndrome in acute pancreatitis - Wilden, Anika; Glaubitz, Juliane; Otto, Oliver; Biedenweg, Doreen; Nauck, Matthias; Mack, Matthias; Ribback, Silvia; Bröker, Barbara M.; Rheinbaben, Sabrina Freiin von; Lerch, Markus M.; Aghdassi, Ali Alexander; Weiss, Frank Ulrich; et al. (Frontiers in Immunology, 2022)
Objective Acute pancreatitis (AP) is an inflammatory disorder, the severe form of which is burdened with multi-organ dysfunction and high mortality. The pathogenesis of life –threatening organ complications, such as respiratory and renal failure, is unknown. Design Organ dysfunction was investigated in a mouse model of AP. The influence of monocytes and neutrophils on multi organ dysfunction syndrome (MODS) was investigated in vivo by antibody depletion. Using real-time-fluorescence and deformability-cytometry (RT-DC) analysis we determined the mechanical properties of neutrophils and monocytes during AP. Furthermore, blood samples of pancreatitis patients were used to characterize severity-dependent chemokine profiles according to the revised Atlanta classification. Results Similar to AP in humans, severe disease in the mouse model associates with organ dysfunction mainly of lung and kidney, which is triggered by a mobilisation of Ly6g-/CD11b+/Ly6c hi monocytes, but not of Ly6g+/CD11b+ neutrophils. Monocyte depletion by anti-CCR2 antibody treatment ameliorated lung function (oxygen consumption) without interfering with the systemic immune response. RT-DC analysis of circulation monocytes showed a significant increase in cell size during SAP, but without a compensatory increase in elasticity. Patient chemokine profiles show a correlation of AP severity with monocyte attracting chemokines like MCP-1 or MIG and with leukocyte mobilisation. Conclusion In AP, the physical properties of mobilized monocytes, especially their large size, result in an obstruction of the fine capillary systems of the lung and of the kidney glomeruli. A selective depletion of monocytes may represent a treatment strategy for pancreatitis as well as for other inflammation-related disorders.